Resist-and-release sprint running using parachute towing causes detrimental changes to performance, kinematics, and kinetics - Gleadhill, S.; Kai, T.; Nagahara, R. (Journal of Physical Education and Sport, 2020)
Resist-and-release (RAR) using parachute towing (PT) describes running while towing a parachute to apply resistance, before releasing the parachute and continuing to sprint. The release instant is typically performed manually via pulling a Velcro strap, and may influence sprint characteristics. The purpose of this study was to clarify performance, kinematic and kinetic changes due to RAR during sprinting using PT. Ten university club athletes performed 60 m RAR trials using PT over a long force platform system. Paired t-tests, significance set to P < .010, and effect sizes ±95% confidence intervals were calculated to compare sprint characteristics between steps before verse after releasing resistance within RAR trials (five pairs). Main findings showed non-significant (P = .015, P = .040) trivial running speed changes for the 1st-2nd steps before and after releasing resistance, compared to the 3rd-4th steps before release. Step length demonstrated non-significant (P = .752) trivial changes for the 1st-2nd steps after releasing resistance, compared to the 3 rd-4th steps before release. Step frequency had a significant (P < .001) moderate decrease at the 1st-2nd steps before release, compared to the 3rd-4th steps before release. Anteroposterior net impulse demonstrated significantly (P < .001) large decreases for all steps after release, compared to the 3rd-4th steps before release. Taken together, results suggested that detrimental changes to sprint characteristics occurred at the 1st-2nd steps before or after manually releasing resistance within RAR trials using PT. Recommendations for sprint coaches included avoiding manual release RAR using PT or being wary of these possible detrimental sprint characteristic changes during the two steps before and/or after the release instant.